(untitled) - Denis P Dykstra (Rome, 1996)
The information provided in this model code of forest harvesting practice has been compliled with intent of highlighting the wide range of environmentally sound harvesting practices that are available to forest managers, especially those requiring only a modest level of investment in training and technology. This will permit policy-makers to develop national, regional or local codes of practice which will best serve the particular needs of government agencies, the private sector, non-governmental organizations and other constituents.
Keywords: forests,harvesting